PENGARUH KEPEMIMPINAN, KEPUASAN KERJA, DAN KOMPETENSITERHADAP KINERJA KARYAWAN KSU DANA RAHAYU - I Ketut Candra Putra; I Wayan Suarjana; Bagus Nyoman Kusuma Putra (VALUES, 2023)
Human resources are a central factor in an organization. Whatever the form and purpose, the organization is made based on various visions for the benefit of humans and in carrying out its mission it is managed and managed by humans. One of the factors that can affect employee performance is leadership, job satisfaction andcompetence. This study aims to determine the effect of leadership, job satisfaction and competence on the performance of KSU Dana Rahayu employees The population in this study were 30 people. The sample in this study were 30 employees at KSU Dana Rahayu. Determination of the sample in this study is saturated sampling, in which theentire population is used as a sample. The analysis technique used is Multiple Linear Regression Analysis. The results of this study indicate that the leadership variable hasa positive and significant effect on employee performance, job satisfaction has a positive and significant effect on employee performance, and competence has a positiveand significant effect on employee performance at KSU Dana Rahayu.